AKIBAT HUKUM TERHADAP AKTA JAMINAN FIDUSIA YANG TIDAK DIDAFTARKAN PADA BANK PERKREDITAN RAKYAT (BPR) TUAH NEGERI MANDIRI PEKANBARU - Harris, Alfian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Guarantee is required by financial institutions (both banks and non-bank) in order to loan / credit to the individual or business entity to guarantee the repayment of credit both for short term and long term if the debtor defaults. One of the security agency, known in the legal system in Indonesia is the guarantee of fiduciary institution.. In this fiduciary agreement notaril deed needed to be registered with the Registry Office will issue a certificate of fiduciary fiduciary. However, in practice in the field are still many certificates notaril fiduciary agreement that is not registered, so Bank Indonesia as supervisor of banks and financial institutions in Indonesia should give ultimatum to banks and financial institutions that do not register the deed of fiduciary to the registration office fiduciary. Based on the research results of the legal consequences of fiduciary warranty deed is not registered with the Rural Banks (BPR) State Tuah Mandiri Pekanbaru is legal uncertainty, the absence of registration of fiduciary obligations that caused fiduciary does not meet the elements of publicity, so it is difficult to control. This can lead to things that are not healthy in practice, such as the existence of a fiduciary twice without the knowledge of its creditors, the transfer of the goods without the knowledge of the creditors, and others. Advice, the need for increased surveillance and sanctions from the Bank Indonesia to banks and financial institutions, especially in the field of fiduciary deed registration so that the implementation of the rules that have been set in accordance with what was expected later.